From virtue epistemology to epistemic happiness - Jaume, Andrés L. (Logos. Anales del Seminario de Metafísica, 2024)
This article aims to overcome the division between a reliabilist epistemology and a responsibilist one. Instead, it presents an organic view of human knowledge. The organic view, also known as pre-cismatic, integrates reliabilist and responsibilist aspects. Finally, a new concept is discussed: epistemic happiness, which is justified from an agentive perspective of knowledge. Thus, it is argued that it seems reasonable to think of knowledge as a type of action which ultimate goal is happiness. This happiness can be obtained through negative means - by not obtaining truth but improving the epistemic situation - or through positive means, i.e., when it hits the target of truth.
Keywords: Aquinas; epistemic reliabilism; epistemic happiness; epistemic responsibility; epistemic teleology; epistemic virtue; Sosa; Zagzebski